A “ERA PELLANDA” EM TRÊS ATOS: A DIOCESE DE PONTA GROSSA-PR. DURANTE O EPISCOPADO DE DOM GERALDO MICHELETTO PELLANDA (1962-1979) - Nascimento, Siderlei (2011)
The present study sought to understand the positioning of the Diocese of Ponta Grossa-PR before the changes provided by the Second Vatican Council, which discussed the integration of the Catholic Church to modernity, the appreciation of the particular churchand lay participation. In the city of Ponta Grossa-PR., Diocesan seat, there was the embodiment of the Pastoral Plan for the 1978/1979 biennium, aimed at the formation of Basic Ecclesial Communities, which undertook, with the evangelization liberating and transformative social structures. However, when oral narratives articulate individuals who experienced the historical period, in various social settings of the diocese, we measurethe constraints of the diocesan bishop with regard to the social movements of the church in relation to the participation of church members on issues of local politics , and the preferential option for the poor. From this discussion, we conclude that the materialization of this pastoral plan was effective, more as an instrument of legitimation of the power of the religious specialist, than to the Catholic church linked to social movements.